Pengaruh Customer Marketing Relationship, Kelompok Referensi, dan Kualitas Layanan terhadap Kepuasan serta Loyalitas Anggota Koperasi (Studi pada Koperasi Rimba Mutiara Banso, Kabupaten Siak) - Junaidi; Fitriana Apriliiaty; Geby Fadilla Yuza; Dian Wahyuni; Diki arisandi; Mizan Asnawi (EL-EMIR Institute, 2026)
This study aims to analyze the influence of customer marketing relationships, reference groups, and service quality on the satisfaction and loyalty of members of the Rimba Mutiara Banso Cooperative in Siak Regency. The study employed a quantitative approach with a survey method involving all 61 cooperative member group leaders, thus employing a census sampling technique. Data were collected using a Likert-scale questionnaire and analyzed using the SEM-PLS method. The results showed that customer marketing relationships, reference groups, and service quality significantly influenced cooperative member satisfaction. Furthermore, customer marketing relationships, service quality, and member satisfaction were shown to significantly influence member loyalty, while reference groups had no direct effect on loyalty. These findings confirm that member satisfaction plays a strategic role as a mediating variable in strengthening the influence of marketing relationships and service quality on cooperative member loyalty. The novelty of this study lies in the simultaneous examination of the relationship between customer marketing relationships, reference groups, and service quality on loyalty, with satisfaction as an intervening variable in the context of plantation-based Islamic cooperatives, a practice still relatively limited in cooperative management studies. Practically, the results of this study provide implications for cooperative managers to prioritize strengthening sustainable marketing relationships and improving service quality as key strategies for maintaining member satisfaction and building long-term loyalty.